Combretum species around Africa as alternative medicine: Ethnopharmacological and ethnobotanical importance - Ikechukwu P. Ejidike, Fanyana M. Mtunzi, Imelda Ledwaba, Mokete J. Phele, Obiamaka M. Ejidike, Oluwaferanmi Ogunleye, Athar Ata, Michael O. Eze (Journal of Applied Pharmaceutical Science, 2023)
Herbal medicine is a form of medicine that has been extensively exploited in traditional medicine, and its therapeutic potential is accepted. Combretum is one of the most frequently happening genera in the African and Asia tropical and subtropical areas; some are widely used in African herbal medicine due to their ethnopharmacological properties. Numerous species of this plant have been used and expended owing to high pharmaco-constituents following their phytochemical screening and evaluations. The recent incidence of multidrug-resistant strains and reduced receptiveness to antibiotics has raised serious anxiety in health delivery and the need for an urgent search for new antibiotics mediators from nature. A countless number of natural substances have resulted from the Combretum species as medicine and are utilized traditionally for the management of bacteriological infection. The plants have received comprehensive documentation as a good cradle of natural constituents that can be categorized into four groups following their biosynthetic source: alkaloids, terpenoids, polyketides, and phenylpropanoids. The study deals with the ethnobotanical and pharmacological significance of the Combretum species for treating numerous ailments and diseases.
Keywords: Ethnopharmacological, Combretum species, ethnobotanical, triterpenoids, therapeutic potentials, pharmaco-constituent